Instrumentation and use of rhythm in Cindai by Pak Ngah / Muhammad Hilmi Nazli - Nazli, Muhammad Hilmi (2023)
This study aims to analyze the instrumentation and use of rhythm in the Malay traditional song "Cindai" by Pak Ngah. The analysis is conducted by examining the song's structure and various sections, including the intro, verse, chorus, and instrumental breaks. The study focuses on Pak Ngah's use of traditional Malay instruments and the ways he blends these with contemporary instruments to create a unique sound. Additionally, the study examines how Pak Ngah employs different rhythms and their effects on the song's overall feel and impact. The results of the analysis reveal how Pak Ngah's creative instrumentation and skillful use of rhythm create a compelling and memorable musical experience. This study highlights the importance of creativity, innovation, and the conservation of traditional musical elements in creating music that resonates with audiences while still maintaining a strong cultural identity.